2017
DOI: 10.1002/hup.2644
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 and CYP2D6 polymorphisms and treatment response of psychotic patients in a naturalistic setting

Abstract: Objectives: The aim of our study was to examine the association between ABCB1 polymorphisms G2677T/A (rs2032582) and C3435T (rs1045642) and common CYP2D6 variants, with the response to antipsychotic treatment of psychotic patients, in a naturalistic setting, in Greece.Methods: One hundred patients suffering from schizophrenia and other psychotic disorders were included in the study. Dosages were normalized to chlorpromazine equivalents. Response following 1 month of treatment was assessed as either a continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
1
5
0
1
Order By: Relevance
“…Studies relying on large sample size underlined increased weight gain [51], prolactin levels [77], risk of EPS [71], and impaired treatment response [52] in patients deprived from at least one functional allele for CYP2D6, resulting in increased drug exposure. While the findings regarding movement abnormalities and lack of therapeutic effect concur with existing evidence [84,85], AIWG [86] and hyperprolactinemia [87] were not consistently linked with CYP2D6 impairments. However, olanzapine is mostly metabolized by CYP1A2 (and to a lesser extent by CYP2D6 and CYP3A4) [88,89], clozapine is mainly metabolized by CYP3A4 and CYP1A2 (with CYP2D6 playing a minor role) [16,90], and loxapine is primarily metabolized by CYP1A2 (then by CYP3A4 and CYP2D6) [19].…”
Section: Discussionsupporting
confidence: 79%
“…Studies relying on large sample size underlined increased weight gain [51], prolactin levels [77], risk of EPS [71], and impaired treatment response [52] in patients deprived from at least one functional allele for CYP2D6, resulting in increased drug exposure. While the findings regarding movement abnormalities and lack of therapeutic effect concur with existing evidence [84,85], AIWG [86] and hyperprolactinemia [87] were not consistently linked with CYP2D6 impairments. However, olanzapine is mostly metabolized by CYP1A2 (and to a lesser extent by CYP2D6 and CYP3A4) [88,89], clozapine is mainly metabolized by CYP3A4 and CYP1A2 (with CYP2D6 playing a minor role) [16,90], and loxapine is primarily metabolized by CYP1A2 (then by CYP3A4 and CYP2D6) [19].…”
Section: Discussionsupporting
confidence: 79%
“…ABCB1 has also been studied regarding efficacy. Papazisis et al [17] found an involvement of ABCB1 in the evolution of PANSS, but only in patients with decreased CYP2D6 activity, and also only for the rs2032582 (2677G>T/A) polymorphism in ABCB1, but not rs1045642 (3435C>T), which is the one used in the present study. Other authors, however, have been able to find an effect of 3435C>T on clinical improvement [18,40] .…”
Section: Discussionmentioning
confidence: 55%
“…For CYP2D6, there are negative reports [15] , although it has also been reported that improvement of the condition is affected by the metabolizing phenotype [7,16] . The situation is similar for ABCB1, with some studies having found association [17,18] with antipsychotic responses while others have not [19] . There have also been reports of association with genetic variation in CYPs and ABCB1 with adverse effects [20][21][22][23] .…”
Section: Introductionmentioning
confidence: 87%
“…Consensus on the association between ABCB1 SNPs and drug response has been lacking, due to their unclear effect on protein expression and activity, with no established clinical indication for analysis of variants. Despite this, in a recent study, Papazisis and colleagues conclude that an interaction between ABCB1 and CYP2D6 might affect patients’ response to antipsychotic treatments . Indeed, patients carrying a combination of a loss of function (LOF) CYP2D6 allele and an ABCB1 rs2032582 TT genotype presented a significantly worse response to antipsychotic drug treatment compared to non‐carriers.…”
Section: Discussionmentioning
confidence: 98%